2022
DOI: 10.1111/jcmm.17517
|View full text |Cite
|
Sign up to set email alerts
|

Systematic pan‐cancer analysis identifies RBM39 as an immunological and prognostic biomarker

Abstract: RNA‐binding Motif Protein39 (RBM39) is identified as a splicing factor and transcription coactivator. Despite mounting evidence that RBM39 plays a critical role in the development of specific malignancies, no systematic pan‐cancer investigation of RBM39 has been conducted. As a result, we set out to investigate RBM39’s prognostic significance and putative immunological activities in 33 different cancers. Based on TCGA and CCLE, GTEx, cBioportal and HPA, we used a series of bioinformatics approaches to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Previous studies have also shown that RBM39 is a proto-oncogene that plays an important role in the development of malignant tumors [42]. Recent studies have found that RBM39 has been identi ed as a marker of pan-cancer and is negatively correlated with in ltration of most immune cells [43]. In particular, RBM39 expression was substantially associated with tumor stage and MSI, which is similar to the ndings of this study.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have also shown that RBM39 is a proto-oncogene that plays an important role in the development of malignant tumors [42]. Recent studies have found that RBM39 has been identi ed as a marker of pan-cancer and is negatively correlated with in ltration of most immune cells [43]. In particular, RBM39 expression was substantially associated with tumor stage and MSI, which is similar to the ndings of this study.…”
Section: Discussionsupporting
confidence: 89%
“…Recent reports revealed that TME plays critical functions in tumour progression and influences final prognosis [ 41 ]. Furthermore, reports have demonstrated that TME is associated with various cancer genes [ 42 ]. Our results indicated that EDIL3 was highly associated with the levels of various tumour-infiltrating immune cells in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Increased RBM39 expression has also been identified across a host of solid tumors and hematologic malig-nancies [103]. A pan-cancer analysis of RBM39 correlates expression with clinical outcome for patients in terms of overall survival, dependent on tumor type [104]. Additionally, RBM39 has been proposed as a unique vulnerability in leukemias bearing splicing factor mutations [105].…”
Section: Targeting Rna Binding Proteinsmentioning
confidence: 99%